EFFECT OF BEDDING PLANES ON SLOPE STABILITY IN COAL OPEN MINE PT. PAMAPERSADA NUSANTARA DISTRICT ASMI, CENTRAL KALIMANTAN - Akbar, Faisal; Sophian, Raden Irvan; Muslim, Dicky; Manullang, Sahala (Faculty of Geological Engineering, Universitas Padjadjaran, 2020)
Bedding planes are one of the distinctive features of an open coal mine. The presence of the bedding planes can be a slip surface on a slope that has a dip direction relatively in the same direction as the bedding planes. Kinematic analysis for open pit slopes is one important aspect of the influence of the bedding planes in minimizing the occurrence of landslides. The purpose of this research is to explain the effect of the presence of bedding planes on slope stability. The method used is secondary data collection, field observations, and kinematic analysis. The results showed that the slopes of the study area were composed of sandstone, claystone, siltstone, carbonaceous claystone, and coal. Carbonanaceous claystone as a weakly layer. The rock bedding area on this slope has a strike/dip N 288 ° E / 17 °, while the slope of the research has an overall slope 29 ° and a slope dip direction N 15 ° E. The dip direction value that is relatively unidirectional between the bedding planes and the slope of the research with a difference of 3 ° can be the cause of the slip surface and is prone to landslides. Thus, the slopes of the study area have the potential plane failure so that geotechnical engineering is needed in the next mining process to ensure slope stability.